DOMESTIC VIOLENCE AND FAMILY RELATIONSHIPS. A FEW LEGAL, SOCIAL AND PSYCHOLOGICAL CONSIDERATIONS - Ioana PĂDURARIU; Vasile COMAN (Challenges of the Knowledge Society, 2023)
Domestic violence is a serious problem (even a criminal offense under Romanian law) that affects a lot of people around the world, has implications in criminal matters, but also in the field of family law, and transcends national law, with implications at the European level as well. We recall here the convictions for the payment of moral damages before ECtHR. In Romania, domestic violence is regulated primarily by Law no. 217/2003 on preventing and combating domestic violence, but there are also some other provisions related to domestic violence in the Civil Code (Law no. 287/2009) and in the Criminal Code (Law no. 286/2009), as well as in other special laws, such as Law no. 272/2004 on protection and promotion of the rights of the child and Law no. 273/2004 regarding the procedure of adoption. At the European level, we can mention Directive 2011/99/EU on the European Protection Order (EPO), a mechanism for the mutual recognition of protection measures of victims of crime, and we will note that, despite the laudable intentions of the EPO Directive, the aim of which is to provide continuous and similar protection of victims when they are moving across Member States, there are many reasons why the EPO remains under-used in practice. Therefore, the chosen topic aims to find an answer to the question of whether the measures to combat domestic violence are sufficient and effective, both those regulated by national legislation and those provided for in international treaties.